Tantangan dan Peluang Guru PAI dalam Menerapkan Kurikulum Merdeka Belajar sebagai Upaya Mewujudkan Program Suistainable Developments Goals - Indry Nirma Yunizul; Maemunah Sa’diyah (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2024)
This research aims to investigate the implementation of the Independent Curriculum and Sustainable Development Goals (SDGs) in Indonesia with a focus on the role of Islamic Religious Education (PAI) teachers. The Independent Curriculum is an educational initiative that gives schools and teachers freedom to develop curricula and learning methods to improve the quality of education. SDGs, on the other hand, are global programs aimed at achieving sustainable development throughout the world. The research method used is a qualitative approach by collecting data from various literary sources, including books, articles, documentation, magazines and newspapers. The research results show that the implementation of the Independent Curriculum consists of three stages: Independent Learning, Independent Change, and Independent Sharing. PAI teachers face challenges in understanding the SDGs and integrating them into the PAI curriculum. However, they also have the opportunity to link religious values ​​with SDGs principles in learning. This research concludes that PAI teachers have a key role in achieving sustainable development goals by integrating religious values ​​with SDGs principles. By collaborating with pioneer schools that have successfully adopted the Independent Curriculum, PAI teachers can become important agents of change in efforts to realize the SDGs program in Indonesia.